Lietuvių spaudos veikėjas Martynas Jankus - Stonienė, Vanda (Knygotyra, 1973)
M. Jankus (1859–1946) was a well-known editor and printer of Lithuanian books and newspapers in Germany at the end of the 19th century and in the first decades of the 20th century. He worked under extremely difficult conditions of Lithuanian cultural life (the Lithuanian press ban etc.). He helped much in editing and printing the main Lithuanian newspapers of that time (“Aušra”, “Varpas”). He himself has edited some newspapers (“Garsas”, “Tetutė”, “Saulėtaka”, etc.). M. Jankus has published about 350 Lithuanian books, leaflets, etc. His house in Bitėnai once became the printing base of the Party of the Lithuanian Social Democrats. The organs of the press of this party were being issued there for some time. In M. Jankus’ printing-house the first Lithuanian edition of “The Communist Manifesto” by K. Marx and F. Engels, some works of the prominent Lithuanian revolutionary V. Kapsukas were published. The Belorussian revolutionaries made also use of his printing-house.M. Jankus was often engaged with the spreading of the issues of the Lithuanian press prohibited and prosecuted severely by the tsarist Russian authorities. He used to organize the illegal transportation of Lithuanian books and periodicals to Lithuania. In general M. Jankus tried to help the Lithuanian people to fight both against the germanisation and the tsarist policy.